The vitality plan - Bull, Deborah (A Dorling Kidersley, 1998)
The book demonstrates how this choice is available to everyone, without the need for joining an expensive gym or buying the latest fitness gimmicks. The crucial difference between aerobic and anaerobic exercise is defined, and the benefits of sustained, low-impact aerobic exercise are explained in full. Excercise, strength-training and stretching plans are set out for people of any fitness level, and additional vital information, such as reading your heart rate and refuelling, is also provided. Photographic sequences demonstrate simple yet effective execises that are easy for the reader to follow.